Ethnicity, National Integrity and Monument in Argal - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2008)
In Nepal, social inclusion, ethnic identity, positive discrimination and proportional representation being burning issues now. Ethnic identity is a vital element of discussion for social inclusion, positive discrimination and proportional representation. Assertion on ethnic identity, seeks recognition from concerned institutions, practices traditions and advocates their ethnic right on socio-economic and political power. These issues are intrinsically linked to national integration. To be sure, very little attention is paid toward ancestral monuments of the past. Monuments vary by their size, pattern, investment, management, and range of dissemination. Local level monuments have little possibility to attract the attention of people of various places and interest, unless they have becomes extraordinary significance. In order to understand monumentality in wider social context, it is very important to look at the village level society. Monument building in Nepal has been linked to culture, history, religion, ethnic identity as well as social system. Argal VDC of Baglung district of Nepal represent with multi-ethnic/caste setting that has high influence over the nature of monument and the rituals performed. In multiethnic setting economic, social, and political activities co-exist, each nourishing the other. Key Words: Ethnicity, Argali Magars, Intra-ethnic relation, Magars, Monuments, National Integrity, Nepal DOI = 10.3126/dsaj.v2i0.1359 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.101-120